Pegembangan Media Pembelajaran Berbasis Focusky Pada Mata Pelajaran Geografi Materi Keragaman Budaya Indonesia Kelas XI Di SMA Negeri 1 Tilango, Kecamatan Tilango, Kabupaten Gorontalo - Monalisa Bakari; Sri Maryati; Rusiyah Rusiyah (JPG (Jurnal Pendidikan Geografi), 2023)
Monalisa Bakari. 2022. "Development of Focusky-based learning media on Geography Subjects on Indonesian Cultural Diversity at SMA Negeri 1 Tilango, Tilango District, Gorontalo Regency". S1 Thesis, Department of Earth Science and Technology, Faculty of Mathematics and Natural Sciences, State University of Gorontalo. Advisor 1: Dr. eng. Sri Maryati, S.Si, Advisor 2: Rusiyah, S.Pd., M.Sc. This study aims to develop a focusky media on the material of Indonesian cultural diversity in class XI IPS. The development model used in this research is the ADDIE model. Data collection techniques through observation, interviews, questionnaires and documentation. The instrument used in the form of assessment criteria to determine the feasibility of the media from media experts, material experts and learning experts as well as student responses to learning media and suggestions for revision. The results of the material expert validation got a score of 61.6% at the beginning of the revision, then revised again to get a percentage value of 71% with the validity level being in a valid qualification, the validation results by media experts getting a value of 90.99% with a very high level of validity entering the qualification valid, and the results of the validation by learning experts get a score of 97% with the validity level being included in a very valid qualification. As for student responses from the results of the limited scale trial getting a value of 81.57% this value is included in the very valid category, then student responses from the general scale trial get a value of 88.9%, this value is included in the category very good.